Testing the stress-buffering hypothesis of sensation seeking in a controlled experimental setting. (1st December 2019) - Roth, Marcus; Liebe, Nico; Altmann, Tobias
Abstract: Because sensation seeking is characterized by a seeking of intense stimulation and novel sensations and experiences, previous studies have suggested that high sensation seekers are less impaired by stressful events. In the present study, we examined the extent to which sensation seeking has a stress-buffering effect in the context of working on a sustained attention task under changing noise conditions. We focused on direct stress outcomes, which were operationalized by parameters on three different levels of observation (subjective experience via self-reports, biophysiological parameters, and performance measures). Our findings only reveal the hypothesized buffering effect for self-reported negative affect. However, contrary to our hypothesis, we found no evidence for any stress-moderating effect of sensation seeking in objective data (biophysiological parameters and performance measures) and self-reported stress experience. These findings were independent from the inventory we used to measure sensation seeking.